USING OF Porcellio sp. AS A BIOINDICATOR TO MUEASURING THELEVEL OF SOME HEAVY METAL POLLUTION IN BAGHDAD CITY - Al-Ameen, Nadya (Iraqi Journal of Science, 2024)
The aim of this study is to estimate the pollution levels of heavy metals by using thegenus porcellio sp.as a bioindicator to this pollution.Four experimental sites in Baghdad were selected (Jadrya, Al-sadr, Al-dura and Algazalya).the genus individuals were take from the soil of these places and dried thenanalyzed by the Absorption Sepctrophotometry. Seven heavy metals measurd theyincludes (Pb ,Cu ,Fe ,Mn ,Ni ,Cd and Co).The results showed that there was a pollution in these places and the higher levels inJadrya were in (Cu 8166±0.33 , Mn 5963±0.44 , Cd146±0.08) μg/gm, in Al-sadrcity were in (Fe 99801±1.15, Co 220±0.15) μg/g in Al-dura was in (Ni416±0.08)μg/g and in Al-gazalya were in (Pb6966±0.88 , Co233±0.12) μg/g .This pollution ofheavy metals was a natural result because of the traffic activity and the increasing ofthe car numbers which still using the lead gasoline and this caused big troubles tothe environment, dangerous to the human.Beside the human activities, recent the green zones is important in decreases the damages of heavy metals on theenvironment.